Positive rates of hepatitis E virus IgG antibodies in pregnant women in China: a meta-analysis - Qixin XIE; Chunmei YE; Zhaojun LU; Wenwen GU; Jing WANG; Jian DU; Yingying YANG; Yan LIU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the positive rate of hepatitis E virus (HEV) immunoglobulin G (IgG) antibodies in pregnant women in China and to provide a reference for the prevention and control of hepatitis E in the women. MethodsPubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data were searched, supplemented by a retrospective literature search, to collect relevant literature published domestically and internationally from January 1, 1989, to December 31, 2023, on the seroprevalence of HEV in pregnant women in China. R 3.5.2 software was used for meta-analysis of the included literature. ResultsA total of 15 articles (8 in Chinese and 7 in English) were included, with a cumulative study population of 36 188. The meta-analysis showed that the positive rate of HEV IgG antibodies among pregnant women in China was 13% (95% confidence interval [95%CI]: 11%–16%). Subgroup analysis showed that the positive rates of HEV IgG antibodies in pregnant women younger than 30 years old and 30 years old and older were 18% (95%CI: 12%–24%) and 15% (95%CI: 10%–19%), respectively; the positive rates of HEV IgG antibodies in pregnant women living in urban and rural areas were 29% (95%CI: 3%–55%) and 25% (95%CI: 5%–45%), respectively; and the positive rates of HEV IgG antibodies in pregnant women in the first, second, and third trimesters were 16% (95%CI: 3%–28%), 13% (95%CI: 7%–18%), and 15% (95%CI: 10%–21%), respectively. There were no statistically significant differences in the positive rates of HEV IgG antibodies among pregnant women of different ages, residences, and gestational ages (all P>0.05). Sensitivity analysis and publication bias tests showed that there was no publication bias in the literature included in this meta-analysis, and the results were relatively stable. ConclusionsThe positive rate of HEV IgG antibodies among pregnant women in China is relatively high. Attention should be paid to this high-risk group, and prevention and control measures for HEV infection should be strengthened.